Shifting Comparative Advantages : Implications for Growth Strategy - Coulibaly, Souleymane (World Bank, Washington, DC, 2012)
The future development of the Tajik economy will be shaped by its comparative advantage on world markets. Exploiting comparative advantage enables an economy to reap gains from trade. Tajikistan's most important comparative advantage is its hydropower potential, which is far larger than the economy's domestic requirements. Yet, high capital costs of building hydropower plants and the unstable geopolitical situation in the transit region to reach South Asian export markets are constraining the realization of this potential. In the short term, the sector, which provides the greatest opportunity for Tajikistan to diversify its exports, appears to be agro-industry and, to a lesser extent, clothing. For both sectors, the main export market is likely to be the regional market. Tajikistan also has a comparative advantage in labor exports, which it has successfully exploited since the mid-2000s. To harness the full potential for labor exports will require improving the skills base of migrant workers and, in particular, their command of the Russian language. In the medium term, the paper argues that an export diversification strategy should tap the agglomeration economies generated by cities. More specifically, establishing Tajikistan's two leading cities, Dushanbe and Khujand, and their surroundings as enclave economies, linked to each other and to major regional markets through improved transport infrastructure so as to minimize production and transportation costs. The two enclave economies should provide the supporting services (finance, logistics, transport and storage) for private sector businesses. In the long term, regional cooperation on trade and transport facilitation could be pursued to reduce transport costs to attractive regional markets such as China, India, Russia and Turkey.